Bildung as the process of cultural heritage: two traditions under a single name - Visa Immonen (United Kingdom, 2025)
In this article, I describe the 19th-century Finnish philosopher Johan Vilhelm Snellman’s ideas about Bildung, and show how this concept provided another basis for cultural heritage, which diverges from how the term was used after the 1960s and 1970s. Bildung refers to the historically unfolding process in which humanity, nations, and individuals, through their own efforts, become what they are. It is the movement towards self-realisation. As parts of this process, immaterial and material objects become meaningful, human entities, and consequently the value of cultural phenomena is to be estimated on the basis of their contribu- tion to Bildung. The Bildung tradition conceptualises cultural heritage in ways that avoid some of the present dichotomies and problems, but it also introduces complications of its own.